Anti-Tumor Effect and Mechanism Study of Caloric Restriction, Achieved by Time-Restricted Feeding, in Mice - Weisheng Lu BSc; Jue Wang; Chengji Wang BSc; Haijie Wang BSc; Wenhao Gao; Shouchong Ye MS; Ruling Shen PhD (Cancer Control)
Objective To evaluate the therapeutic effects and explore the mechanisms behind caloric restriction achieved through time-restricted feeding (CR) in inhibiting mouse tumors, providing a theoretical basis and data support for future CR diet-assisted anticancer treatment protocols. Methods C57BL/6 and BALB/c mice were divided into four cell line groups. Each group was further split into normal diet (ND) and a CR diet groups. The ND groups had free access to water and a normal diet, while the CR diet groups had access to water but were only fed from 9 a.m. to 11 a.m., fasting for the remaining 22 h. Food intake was recorded daily starting on day 1 of the experiment. Tumor models were established and assessed every 2 days. Blood biochemical indicators, serum pyruvic acid levels, and cytokine expression were measured. Results The CR diet inhibited tumor growth in mice. Colorimetric assays and ELISAs showed a reduction in pyruvic acid levels and in key upstream and downstream rate-limiting enzymes in the sera of CR mice. Routine blood and blood biochemistry tests suggested minor effects of the CR diet on these parameters. Western blotting revealed that the CR diet suppressed mTOR and AKT protein expression in tumor tissues. ELISA showed that various mTOR-related signaling pathways were downregulated. Immunohistochemistry staining indicated reduced expression of P53, P-AKT, EGFR, and IGF-1 in tumor tissues. TUNEL staining confirmed that the CR diet promoted tumor apoptosis. Conclusion The CR diet inhibited tumor growth by suppressing mTOR and its related upstream and downstream gene signaling pathways, reducing tumor glycolysis, and accelerating tumor cell apoptosis.